Polycyclic aromatic hydrocarbons and oxidative stress markers in the clam Ruditapes decussatus from the Ria Formosa (Portugal) - Barreira, Luísa (2011)
Tese dout., Ciências e Tecnologias do Ambiente, Universidade do Algarve, 2007